The Career Costs of Children - Jérôme Adda; Christian Dustmann; Katrien Stevens (Center for Economic Studies and ifo Institute (CESifo), 2016)
We estimate a dynamic life-cycle model of labor supply, fertility and savings, incorporating occupational choices, with specific wage paths and skill atrophy that vary over the career. This allows us to understand the trade-off between occupational choice and desired fertility, as well as the sorting both into the labor market and across occupations. We quantify the life-cycle career costs associated with children, how they decompose into loss of skills during interruptions, lost earnings opportunities and selection into more child-friendly occupations. We analyze the long-run effects of policies that encourage fertility and show that they are considerably smaller than short-run effects.
Keywords: J13; 330; fertility; labor supply; occupation; dynamic structural model; gender wage gap